2013
DOI: 10.1002/jgrf.20061
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water and sediment supply on the stratigraphic record of alluvial fans and deltas: Process controls on stratigraphic completeness

Abstract: [1] Stratigraphy contains the most complete record of information necessary to quantitatively reconstruct paleolandscape dynamics, but this record contains significant gaps over a range of time and space scales. These gaps result from stasis on geomorphic surfaces and erosional events that remove previously deposited sediment. Building on earlier statistical studies, we examine stratigraphic completeness in three laboratory experiments where the topography of aggrading deltas was monitored at high temporal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 58 publications
(132 reference statements)
2
65
0
Order By: Relevance
“…These factors influence and are recorded in even higher frequency scales, as lagoon level changes (Lagoa dos Patos -300 yr), increased vegetation in dune fields (60 yr) and shoreline erosion (22 yr) (Table 3 -High III from the studies of Toldo Jr. et al 1999, 2004, 2005; Barboza et al 2006;Martinho et al 2008Martinho et al , 2009Martinho et al , 2010Dillenburg et al 2017 in press). As already observed in experimental studies, the signal of autogenic processes may be preserved in the stratigraphic record (Paola et al 2009;Jerolmack & Paola 2010;Straub & Esposito 2013;Kim et al 2014).…”
Section: System IVsupporting
confidence: 68%
“…These factors influence and are recorded in even higher frequency scales, as lagoon level changes (Lagoa dos Patos -300 yr), increased vegetation in dune fields (60 yr) and shoreline erosion (22 yr) (Table 3 -High III from the studies of Toldo Jr. et al 1999, 2004, 2005; Barboza et al 2006;Martinho et al 2008Martinho et al , 2009Martinho et al , 2010Dillenburg et al 2017 in press). As already observed in experimental studies, the signal of autogenic processes may be preserved in the stratigraphic record (Paola et al 2009;Jerolmack & Paola 2010;Straub & Esposito 2013;Kim et al 2014).…”
Section: System IVsupporting
confidence: 68%
“…Research in the Delta basin at Tulane University's (Louisiana, USA) Sediment Dynamics Laboratory investigated the completeness of stratigraphic record preservation on experimental alluvial fans and deltas (Straub and Esposito, 2013;Straub and Wang, 2013;Fig. 3).…”
Section: The Impact Of Allogenic Factorsmentioning
confidence: 99%
“…Subject to gradual base-level rise, the experiments demonstrated that environmental signals disconnected from a sediment routing system are best preserved in systems with low surface roughness. Two time scales were proposed by Straub and Esposito (2013) to explain the stratigraphic completeness: the amount of time necessary to generate a deposit to explore topography changes, and the rate of net deposition characterised by the mobility of the channel on the delta tops. They also suggested that stratigraphic completeness in deltaic settings is controlled by the balance of aggradation and lateral channel migrations, with rapid aggradation relative to lateral channel migration leading to high stratigraphic completeness, whereas rapid lateral migration of deep channels relative to system aggradation results in frequent deposit reworking (Straub and Esposito, 2013, p. 12).…”
Section: The Impact Of Allogenic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…FDS typ i cally con sist of a range of sed i men tary en vi ron ments the char ac ter of which strongly de pends on cli mate and tec tonic set ting. The mor phology of FDS re sults from pre-ex ist ing to pog ra phy and in ter play be tween ac com mo da tion rate and sed i ment sup ply (e.g., MacCarthy, 1990;Blair and McPherson, 1994;Harvey et al, 2005;Hickson et al, 2005;Pope and Wilkinson, 2005;Nichols and Fisher, 2007;Blair and McPherson, 2009;Straub and Esposito, 2013;Straub and Wang, 2013). An anal y sis of evo lution of such a depositional sys tem needs a de tailed ap proach with con sid er ation of vari able in put data.…”
Section: Introductionmentioning
confidence: 99%